2021
DOI: 10.1111/biom.13423
|View full text |Cite
|
Sign up to set email alerts
|

Small‐sample inference for cluster‐based outcome‐dependent sampling schemes in resource‐limited settings: Investigating low birthweight in Rwanda

Abstract: The neonatal mortality rate in Rwanda remains above the United Nations Sustainable Development Goal 3 target of 12 deaths per 1,000 live births. As part of a larger effort to reduce preventable neonatal deaths in the country, we conducted a study to examine risk factors for low birthweight. The data was collected via a cost-efficient cluster-based outcome-dependent sampling scheme wherein clusters of individuals (health centers) were selected on the basis of, in part, the outcome rate of the individuals. For a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Letting R k denote the N k × 1 vector with all entries equal to R k , R is the N × 1 vector obtained by concatenating the R k together. Following arguments similar to those presented by Xie and Yang 26 in the complete data setting, Sauer et al 27 showed that under regularity conditions,̂w, the solution to (3), is consistent for 0 , the true value of , and is asymptotically multivariate normal, with the asymptotic variance given by…”
Section: Estimation and Inferencementioning
confidence: 81%
See 2 more Smart Citations
“…Letting R k denote the N k × 1 vector with all entries equal to R k , R is the N × 1 vector obtained by concatenating the R k together. Following arguments similar to those presented by Xie and Yang 26 in the complete data setting, Sauer et al 27 showed that under regularity conditions,̂w, the solution to (3), is consistent for 0 , the true value of , and is asymptotically multivariate normal, with the asymptotic variance given by…”
Section: Estimation and Inferencementioning
confidence: 81%
“…Letting Rk denote the N k × 1 vector with all entries equal to R k , R is the N × 1 vector obtained by concatenating the Rk together. Following arguments similar to those presented by Xie and Yang 26 in the complete data setting, Sauer et al 27 showed that under regularity conditions, β^w, the solution to (), is consistent for β0, the true value of β, and is asymptotically multivariate normal, with the asymptotic variance given by Var[trueβ^w]=H(bold-italicβ0)1true{Varfalse[𝒰wfalse(bold-italicβfalse)false]|β=bold-italicβ0true}H(bold-italicβ0)1, where H ( β ) = − E [∂𝒰( β )], and 𝒰( β ) = U T 1 N ×1 ; see Appendix B of the Supporting Information for details.…”
Section: Settingmentioning
confidence: 82%
See 1 more Smart Citation
“…Given data that has been collected through a single‐stage cluster‐stratified ODS design, estimation and inference can proceed via IPW‐GEE 1,2 . In particular, the regression parameters bold-italicβ$$ \boldsymbol{\beta} $$ can be estimated as the solution to the following: 𝒰wfalse(bold-italicβfalse)=k=1KRkπkbold-italicDkTbold-italicVkprefix−1bold-italicϵk=bold0, where Rk$$ {R}_k $$ is equal to 1 if cluster k$$ k $$ is sampled and is equal to 0 otherwise; πk$$ {\pi}_k $$ is the probability of cluster k$$ k $$ being sampled; bold-italicϵk$$ {\boldsymbol{\epsilon}}_k $$ = false(bold-italicYkprefix−bold-italicμkfalse)$$ \left({\boldsymbol{Y}}_k-{\boldsymbol{\mu}}_k\right) $$, with bold-italicYk$$ {\boldsymbol{Y}}_k $$ = false(Yk1,,YkNkfalse)$$ \left({Y}_{k1},\dots, {Y}_{k{N}_k}\right) $$ and bold-italicμ...…”
Section: Review Of Optimal Allocation In Stratified Cluster‐based Odsmentioning
confidence: 99%
“…One way to operationalize a cluster‐based ODS design is to stratify the clusters based on pieces of information known at the design stage, and to then sample a certain number of clusters from each of the strata. Data that has been collected in such a way can be analyzed using inverse‐probability weighted generalized estimating equations (IPW‐GEE), 1,2 where the weights are the inverse of the cluster‐specific probabilities of selection. The number of clusters sampled from each of the defined strata can influence the efficiency gain or loss for a particular parameter in the analysis model, and Sauer et al 3 derived formulae for the optimal allocation of the (cluster‐level) sample size across the strata, when the intended analysis is IPW‐GEE.…”
Section: Introductionmentioning
confidence: 99%